Assessing the Quality of Knowledge for Adaptation–Experiences From Co-designing Climate Services in Sweden - André, Karin; Järnberg, Linn; Gerger Swartling, Åsa; Berg, Peter; Segersson, David; Amorim, Jorge H.; Strömbäck, Lena (Frontiers in Climate, 2021)
Adaptation to climate change is becoming more urgent, but the wealth of knowledge that informs adaptation planning and decision-making is not used to its full potential. Top-down approaches to knowledge production are identified as one important reason for the gap between science and practice and are criticized for not meeting the needs of intended users. In response to this challenge, there is a growing interest in the creation of user-oriented and actionable climate services to support adaptation. At the same time, recent research suggests that greater efforts are needed to evaluate the effectiveness of knowledge co-production processes and the best criteria by which to gauge the quality of knowledge outcomes, while also considering different stakeholder perspectives. This paper explores these issues through a critical assessment of the quality of knowledge for adaptation generated from a climate services co-design process in two case studies in Sweden. The study draws on experiences from a five-year research collaboration in which natural and social science researchers, together with local stakeholders, co-designed climate services to support climate adaptation planning and decision-making. The well-established knowledge quality criteria of credibility, legitimacy, saliency, usability, and usefulness remain relevant, but are not sufficient to capture factors relating to whether and how the knowledge actually is applied by climate change adaptation planners and decision-makers. We observe that case-specific circumstances beyond the scope of the co-design process, including the decision-making context as well as non-tangible outcomes, also play crucial roles that should be accounted for in the knowledge assessment processes.